Історія вивчення мошок Українських Карпат - Теплюк, Алла; Tepliuk, Alla (Східноєвропейський національний університет імені Лесі Українки, 2016)
Проаналізовано сучасний стан вивчення мошок Українських Карпат. Установлено, що дослідження Simuliidae регіону тривають понад 60 років. З’ясовано, що значний внесок у вивчення мошок у 60-ті роки ХХ ст. зробили В. З. Ковбан і Г. К. Шевченко, а починаючи з 70-х – З. В. Усова, О. Б. Панченко, А. О. Панченко, К. Б. Сухомлін. Згідно з останніми даними К. Б. Сухомлін, симуліїдофауна Українських Карпат нараховує 45 видів із 14 родів. It has been analyzed the modern state of the study blackflies Ukrainian Carpathians. It has been established that the explore of Simuliidae region are continuing for over 60 years. In the 1960s, V. Z. Kovban explored medical-veterinary importance and methods of fighting bloodsucking species of Simuliidae. In 1969 simuliidofauna region totaled 11 species blackflies according to A. K. Shevchenko. In 1973 in the Ukrainian Carpathians Z. V. Usova and A. B. Panchenko registered 42 bloodsucking species and examined their especially of biology and ecology. In 1987 Z. V. Usova already noted 46 species of blackflies for the region. In 2004 A. A. Panchenko summarized the results of his many years of research and data to other scientists, analyzed the systematic names and synonyms, and said that simuliidofauna of Ukrainian Carpathians totaled 56 species. In 2008 K. B. Suchomlin made an audit of own fees and collection funds of the Department of Zoology of Lesya Ukrainka Eastern European National University and Donetsk National University, and clarified that the species composition of blackflies in the region totaled 45 species.
History of the Study Blackflies Ukrainian Carpathians
Keywords: мошки; Українські Карпати; кровососи; видовий склад; фауна; blakflies; Ukrainian Carpathians; bloodsuckers; species composition; fauna